Anti-phospholipid antibody prevalence and association with subclinical atherosclerosis and atherothrombosis in the general population. (1st February 2020) - Selmi, Carlo; De Santis, Maria; Battezzati, Pier Maria; Generali, Elena; Lari, Simone Aldo; Ceribelli, Angela; Isailovic, Natasa; Zermiani, Paola; Neidhöfer, Sandra; Matthias, Torsten; Scirè, Carlo A.; Baldassarre, Damiano; et al.
Abstract: Background: There is no agreement on the prevalence of anti-phospholipid antibodies (aPLs) and the correlation with atherosclerosis and cardiovascular (CV) events in the general population. Methods: We performed a cross-sectional study on 1712 randomly enrolled subjects from a Northern Italian city to investigate the presence of aPLs and the association with subclinical atherosclerosis (using the carotid artery intima media thickness measured as inter-adventitia common carotid artery diameters - ICCAD) and retrospectively collected CV factors and events (i.e. acute myocardial infarction, stroke, and peripheral obliterans arterial vasculopathy) using physician-assisted questionnaires. We tested serum IgG, IgM, and IgA anti -cardiolipin, anti-beta2glycoprotein I (aGPI), and anti -phosphatidylserine-prothrombin antibodies. Results: Positive aPLs were found in 15.1% of the subjects, with no differences between sex but with higher rates in older subjects. Carotid subclinical atherosclerosis was more frequent in aPL positive subjects; more specifically, aGPI IgA were associated with higher ICCAD average (adjusted beta 0.51, 95% confidence interval (CI)0.17–0.84; p = 0.003). A positive history of CV events was also more frequent in aPL positive subjects (odds ratio (OR) 1.67, 95%CI 1.08–2.54; p = 0.012), particularly peripheral obliterans arterial vasculopathy (OR 2.02 ; 95%CI 1.14–3.57; p = 0.015). Among subjects with a Framingham risk score >20, and/or diabetes, and/or body mass index >35 kg/m 2, aPL positivity was associated to the highest risk of CV events (OR 2.52, 95%CI 1.24–5.11; p = 0.011). Conclusions: APL prevalence in the general population is higher than previously reported. CV events and subclinical atherosclerosis are more frequent in the presence of aPL, particularly when a high CV risk coexists. Highlights: Positive aPL are common in the population but their CV significance is unclear. CV events are more frequent in subjects with aPL and an elevated CV risk. aPLs are associated with ultrasound signs of atherosclerosis.